Theoretical progress of groundwater chemical evolution based on Tóthian theory: A review - Dong, Hongzhi; Gao, Zongjun (Frontiers in Marine Science, 2022)
Tóthian theory refers to the gravity driven groundwater flow system (GFS) theory represented by Tóth, which mainly expounds the driving and distribution law of groundwater. The establishment and development of this theory not only deepened people’s understanding of the driving and distribution law of groundwater, but also greatly promoted the study of groundwater chemical evolution (GCE). Modern GCE research is mostly based on Tóthian theory, characterized by combining with advanced scientific and technological means. Based on the clue of time, this paper is divided into two parts. The first part mainly summarizes the establishment and development of Tóthian theory, including the exploration of groundwater driving force and distribution form by hydrogeologists before Tóthian theory, and the enrichment, development and application of Tóthian theory by geologists after its establishment. The second part mainly combs the main theories and application progress of GCE mechanism research, including the main theories and findings of GCE research before the emergence of Tóthian theory, as well as the research progresses of GCE after the emergence of Tóthian theory. With the flow of groundwater in GFS, groundwater undergoes continuous chemical evolution, which eventually leads to the transformation of hydrochemical types and the gradual increase of total dissolved solids (TDS). The distribution of GFS and GCE complement each other. The distribution of GFS directly determines the model of GCE, and the results of GCE also play a certain role in the distribution of GFS. GCE mainly includes dissolution, precipitation, cation exchange and adsorption, which is affected by the physical and chemical conditions of permeable media, organic matter content and microorganisms. GCE has the characteristics of universality, sustainability and diversity. With the increasing global population and the progresses of science and technology, the impact of human life, industrial and agricultural production on groundwater is deepening. The aggravation of pollution directly changes the chemical compositions of groundwater, resulting in changes of the law of GCE.